Fatty Acid Binding Protein 3 Is Involved in n–3 and n–6 PUFA Transport in Mouse Trophoblasts. Issue 10 (13th August 2014) - Islam, Ariful; Kagawa, Yoshiteru; Sharifi, Kazem; Ebrahimi, Majid; Miyazaki, Hirofumi; Yasumoto, Yuki; Kawamura, Saki; Yamamoto, Yui; Sakaguti, Syuiti; Sawada, Tomoo; Tokuda, Nobuko; Sugino, Norihiro; et al.
Abstract: Background: Low placental fatty acid (FA) transport during the embryonic period has been suggested to result in fetal developmental disorders and various adult metabolic diseases, but the molecular mechanism by which FAs are transported through the placental unit remains largely unknown. Objective: The aim of this study was to examine the distribution and functional relevance of FA binding protein (FABP), a cellular chaperone of FAs, in the mouse placenta. Methods: We clarified the localization of FABPs and sought to examine their function in placental FA transport through the phenotypic analysis of Fabp3 -knockout mice. Results: Four FABPs (FABP3, FABP4, FABP5, and FABP7) were expressed with spatial heterogeneity in the placenta, and FABP3 was dominantly localized to the trophoblast cells. In placentas from the Fabp3 -knockout mice (both sexes), the transport coefficients for linoleic acid (LA) were significantly reduced compared with those from wild-type mice by 25% and 44% at embryonic day (E) 15.5 and E18.5, respectively, whereas those for α-linolenic acid (ALA) were reduced by 19% and 17%, respectively. The accumulation of LA (18% and 27% at E15.5 and E18.5) and ALA (16% at E15.5) was also significantly less in the Fabp3 -knockout fetuses than in wild-type fetuses. In contrast, transport and accumulation of palmitic acid (PA) were unaffected and glucose uptake significantly increased by 23% in the gene-ablated mice compared with wild-type mice at E18.5. Incorporation of LA (51% and 52% at 1 and 60 min, respectively) and ALA (23% at 60 min), but not PA, was significantly less in FABP3 -knockdown BeWo cells than in controls, whereas glucose uptake was significantly upregulated by 51%, 50%, 31%, and 33% at 1, 20, 40, and 60 min, respectively. Conclusions: Collectively FABP3 regulates n–3 (ω-3) and n–6 (ω-6) polyunsaturated FA transport in trophoblasts and plays a pivotal role in fetal development.